2019
DOI: 10.1002/pssa.201800832
|View full text |Cite
|
Sign up to set email alerts
|

Electron Sandwich Doubles the Thermoelectric Power Factor of SrTiO3

Abstract: Thermoelectric materials convert a temperature difference into electricity through a phenomenon known as the Seebeck effect, and their efficiency is determined by the dimensionless figure of merit, ZT (≡ S2 · σ · κ−1). Currently, most materials exhibiting high ZT values (ZT > 1) are based on heavy metal compounds, but these materials have low thermal/chemical stability. In this regard, conducting metal oxides attract much attention for thermoelectric power generations at high temperatures based on their advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 74 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…Thermoelectric materials, which convert temperature difference into electricity, have attracted increasing attention in energy harvesting technologies 1‐5 . The efficiency of thermoelectric conversion is characterized by the figure of merit, ZT = S 2 · σ · T · κ −1 , where Z is the figure of merit, T is the absolute temperature, S is the thermopower (≡Seebeck coefficient), σ is the electrical conductivity, and κ is the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoelectric materials, which convert temperature difference into electricity, have attracted increasing attention in energy harvesting technologies 1‐5 . The efficiency of thermoelectric conversion is characterized by the figure of merit, ZT = S 2 · σ · T · κ −1 , where Z is the figure of merit, T is the absolute temperature, S is the thermopower (≡Seebeck coefficient), σ is the electrical conductivity, and κ is the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Available data does not allow to gain further insight into the microscopic nature of plasmon damping mechanisms. However, it turns out that the electron scattering time t ee of SNO, deduced from the measured conductivity and the carrier density, is within a similar range (t ee ≈ 1.4-4.6 × 10 −15 s), depending on the actual effective mass (m* ≈ 1.5 m 0 , as deduced from the corresponding plasma frequency; m* ≈ 0.46 m 0 [19,20] from Seebeck coefficient or DFT) used for calculations. A similar agreement has been reported in Au.…”
Section: Resultsmentioning
confidence: 93%
“…Summary of calculations of the scattering rate in SNO and SVO films. The effective mass m* was either taken from SNO [19,20] and SVO [22][23][24] references, or from the our ellipsometry data (together with dc transport data). The relative permittivity value (ε r = 4) used to calculate the m* from ellipsometric data was taken from Makino et al [24] and is estimated to be nearly identical for SVO and SNO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With proper doping, these materials can be turned into TE materials. For example, it has been found that Nb/La-doped SrTiO 3 shows very high S due to the heavy effective mass of Ti 3d orbital [71][72][73]. Adopting these materials can simultaneously fulfill high S and suitable band structure, bringing enhanced performance.…”
Section: Future Prospectsmentioning
confidence: 99%